Porous material coupled magnesium powder filler and preparation method and application thereof

By using porous materials to couple the filler of magnesium powder and using magnesium and hydrogen as electron donors, the problem of high cost and unsatisfactory treatment filler in the prior art is solved, and a low-cost and efficient nitrate nitrogen removal effect is achieved.

CN119660952AActive Publication Date: 2025-03-21CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311221659.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-03-21
Estimated Expiration
2043-09-21

AI Technical Summary

Technical Problem

In the prior art, the filler used for nitrate wastewater treatment is high in cost, which can easily lead to groove flow or mineralization, and the nitrate nitrogen treatment effect is not ideal.

Method used

The filler of magnesium powder is used to couple the porous material to coordinate the nitrate in water through the autotrophic denitrification process of magnesium and hydrogen as electron donors. The filler consists of magnesium, a porous material, an inorganic carbon source and a binder, and is prepared by solution bonding and drying.

Benefits of technology

It reduces the transportation and storage costs of sewage treatment, avoids the problems of filling sludge and mineralization, improves the removal efficiency of nitrate nitrogen, and has a stable treatment effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660952A_ABST
    Figure CN119660952A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sewage treatment, and provides filler of porous material coupled magnesium powder as well as a preparation method and application of the filler. The filler for coupling the porous material with the magnesium powder comprises 40-60 parts by mass of magnesium, 20-35 parts by mass of a porous material, 5-20 parts by mass of an inorganic carbon source and 5-10 parts by mass of an adhesive. The porous material coupled magnesium powder filler provided by the invention can be used for treating sewage with low carbon-nitrogen ratio, has a good nitrate-nitrogen treatment effect, and solves the problems of high cost and easy channeling or mineralization of the filler.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sewage treatment, and more specifically to a porous material coupled magnesium powder filler and a preparation method and application thereof. Background Art

[0002] Nitrate pollution is one of the most important water quality issues today. Excessive nitrate in drinking water is detrimental to human health and may cause cancer or other diseases. In addition, excessive nitrate in water can also lead to many ecological problems, such as eutrophication of water sources, excessive emissions of greenhouse gas N2O, and deterioration of biological habitats. Heterotrophic denitrification is the mainstream method for removing nitrates from water. This method requires sufficient organic carbon sources in the water, but the carbon-nitrogen ratio of most sewage is low, and organic carbon sources such as methanol, ethanol, and sodium acetate need to be added, which is costly and may cause secondary pollution. In addition, heterotrophic denitrification produces a large amount of sludge, and further treatment leads to increased costs.

[0003] In contrast, autotrophic denitrification can avoid the use of organic carbon sources, thereby reducing costs and secondary pollution, and is very suitable for removing nitrates from low carbon-nitrogen ratio water. Current electron donors mainly include hydrogen, sulfur, iron and its related compounds such as ferrous sulfide compounds and thiosulfate. However, hydrogen is expensive and not suitable for storage and transportation; sulfur and sulfide will produce a large amount of sulfate, and will cause pipeline blockage and ditch flow; iron and its ferrous sulfide compounds have low denitrification efficiency and serious mineralization problems.

[0004] Therefore, it is very meaningful to develop a new electron donor for autotrophic denitrification as a wastewater treatment filler to reduce transportation and storage costs, reduce or avoid mudification and mineralization, and have a more efficient denitrification efficiency. Summary of the invention

[0005] The purpose of the present invention is to provide a porous material coupled magnesium powder filler and a preparation method thereof, so as to solve the technical problems in the prior art that the filler used for nitrate wastewater treatment is high in cost, easy to channel or mineralize, and has unsatisfactory nitrate nitrogen treatment effect.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] In a first aspect, the present invention provides a porous material coupled with a magnesium powder filler, comprising the following components in parts by mass:

[0008] Magnesium: 40-60 parts;

[0009] Porous materials: 20-35 parts;

[0010] Inorganic carbon source: 5-20 parts;

[0011] Adhesive: 5 to 10 parts.

[0012] The magnesium in the filler of the porous material coupled with magnesium powder provided by the present invention exists in the form of elemental magnesium and is combined with the porous material, so that autotrophic denitrifying bacteria grow in large quantities on the surface of the porous material and form a biofilm, and nitrate in water is synergistically treated through an autotrophic denitrification process using magnesium and hydrogen as electron donors.

[0013] The porous material coupled with magnesium powder filler provided by the present invention is applied to sewage treatment, and the autotrophic denitrifying bacteria use the magnesium in the filler and the hydrogen generated by magnesium in water as electron donors to convert nitrate nitrogen in the sewage into nitrogen. The specific reaction process is as follows:

[0014] 5Mg+2NO3 - +6H2O→5Mg 2+ +N2+12OH-

[0015] Mg+H2O→H2+Mg(OH)2

[0016] 5H2+2NO3 - →N2+2OH-+4H2O.

[0017] According to some embodiments of the present invention, the filler particle size is 8 to 12 mm.

[0018] According to some embodiments of the present invention, the porous material includes at least one of a porous structured biological material, a porous structured organic material, and a porous structured inorganic material.

[0019] According to some embodiments of the present invention, the porous structured biomaterial comprises a porous structured natural biomaterial containing cellulose.

[0020] According to some embodiments of the present invention, the porous structure biomaterial includes at least one of sawdust, corn cobs, and grapefruit peels.

[0021] According to some embodiments of the present invention, the porous structure organic material includes at least one of a polyurethane foam material, a polyhedral hollow sphere made of an organic material, and a ball ring made of an organic material.

[0022] According to some embodiments of the present invention, the porous structure inorganic material includes at least one of molecular sieve, zeolite, activated carbon, pumice, rock wool, porous ceramics, and perlite.

[0023] According to some embodiments of the present invention, the inorganic carbon source includes at least one of calcium carbonate, sodium carbonate, sodium bicarbonate, magnesium carbonate, zinc carbonate, and ferrous carbonate.

[0024] According to some embodiments of the invention, the inorganic carbon source includes calcium carbonate, sodium carbonate and sodium bicarbonate.

[0025] According to some embodiments of the present invention, the mass ratio of calcium carbonate, sodium carbonate and sodium bicarbonate is (2-4): (2-3): (3-4).

[0026] According to some embodiments of the present invention, the adhesive includes the following components in percentage by mass: 25-33% ammonium sulfate, 13-15% silica fume, 7-10% sorbitol, 12-15% nitrile rubber, 12-15% butyl acrylate and 20-24% dihydrate gypsum.

[0027] According to some embodiments of the present invention, the preparation method of the adhesive includes: putting butyl acrylate and nitrile rubber into an internal mixer for internal mixing; adding the above-mentioned internally mixed raw materials, ammonium sulfate, silica fume, sorbitol and dihydrate gypsum into a grinder, grinding, and obtaining the adhesive.

[0028] In a second aspect, the present invention provides a method for preparing the filler described in the first aspect, comprising: mixing magnesium powder, porous material, inorganic carbon source, adhesive and water, stirring, granulating, and vacuum drying to obtain the filler.

[0029] The porous material coupled magnesium powder filler provided by the present invention is prepared from raw materials including magnesium powder, porous material, inorganic carbon source and adhesive by a solution bonding and drying method.

[0030] According to some embodiments of the present invention, the particle size of the magnesium powder is 20 to 500 μm.

[0031] According to some embodiments of the present invention, the particle size of the inorganic carbon source is 50 to 500 μm.

[0032] According to some embodiments of the present invention, the stirring time is 1 to 2 hours.

[0033] According to some embodiments of the present invention, the vacuum drying time is 5 to 7 hours.

[0034] According to some embodiments of the present invention, the filler particle size is 8 to 12 mm.

[0035] In a third aspect, the present invention provides an autotrophic denitrification reactor, comprising the filler described in the first aspect or the filler prepared by the preparation method described in the second aspect.

[0036] According to some embodiments of the present invention, the filler occupies 60% to 80% of the volume of the reactor.

[0037] According to some embodiments of the present invention, autotrophic denitrifying bacteria using magnesium and hydrogen as electron donors are selected as the dominant bacteria in the reactor.

[0038] In a fourth aspect, the present invention provides the use of the filler described in the first aspect, the filler prepared by the preparation method described in the second aspect, and the reactor described in the third aspect in sewage treatment; in particular, in treating sewage with a dissolved oxygen concentration lower than 3.0 mg / L and a ratio of COD concentration to nitrate nitrogen concentration (C / N) less than 3.

[0039] The beneficial effects of the present invention are at least:

[0040] (1) The porous material coupled magnesium powder filler provided by the present invention is mainly prepared from magnesium powder, porous material, inorganic carbon source, etc., and the production, transportation and storage costs are much lower than those of hydrogen autotrophic denitrification fillers.

[0041] (2) The magnesium contained in the porous material coupled with magnesium powder filler provided by the present invention and the small amount of hydrogen generated by magnesium in water together serve as electron donors for autotrophic denitrification. There are more types of autotrophic denitrifying bacteria in the system and the bacterial community is more stable, thereby making the denitrification effect of the filler in treating nitrate-containing wastewater more stable.

[0042] (3) The porous material coupled with magnesium powder filler provided by the present invention does not have the problem of filler mudding, and will not cause channeling, pipeline clogging and the like.

[0043] (4) Since magnesium has stronger reducing power than iron, the porous material coupled with magnesium powder filler provided by the present invention is more efficient in treating nitrate-containing wastewater than iron autotrophic denitrification.

[0044] (5) The pH range for magnesium ion precipitation is 9.4 to 12.4. The porous material coupled with the magnesium powder filler provided by the present invention can avoid the mineralization problem caused by iron ion precipitation.

[0045] (6) The porous material coupled with magnesium powder filler provided by the present invention utilizes porous materials, which increases the biofilm position of microorganisms, is more conducive to the attachment of microorganisms, and has physical adsorption properties, which is more conducive to the utilization of nitrate by microorganisms, thereby increasing the ability of unit volume of filler to process nitrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 Schematic diagram of the structure of the reactor used to evaluate the sewage treatment effect of the filler. DETAILED DESCRIPTION

[0047] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.

[0048] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0049] In various embodiments and comparative examples of the present invention, the materials used are as follows:

[0050] Magnesium powder: particle size 50~200μm.

[0051] Calcium carbonate, sodium carbonate, sodium bicarbonate: particle size 50-200μm.

[0052] Iron powder: particle size 50~200μm.

[0053] Sawdust: particle size 1~2mm.

[0054] Corn cob powder: Dry the corn cobs and crush them into 1-2 mm powder.

[0055] Polyurethane foam material: prepared by polyurethane formate, with a pore density of 25ppi and a density of 0.20-0.23g / cm 3 , particle size is 20~60mm.

[0056] Polyhedral hollow ball: Made of polypropylene, specification is DN25.

[0057] Molecular sieve: particle size 50~100μm.

[0058] Zeolite: Natural zeolite, particle size 50-100 μm, specific surface area 300-500 m 2 / g, the packing density is 1.5~2.3cm 3 / g.

[0059] Pumice: Natural pumice, particle size 50-100 μm, specific surface area 100-160 m 2 / g, the packing density is 2.4~3.6cm 3 / g.

[0060] Preparation Example 1

[0061] 12 parts by mass of butyl acrylate and 12 parts by mass of nitrile rubber (powdered nitrile rubber P83) are put into an internal mixer, mixed and stirred evenly; the mixed raw materials are added to a grinder, and 30 parts by mass of ammonium sulfate, 15 parts by mass of silica fume, 10 parts by mass of sorbitol and 21 parts by mass of dihydrate gypsum are added to the grinder, and ground to 25 μm to obtain adhesive A.

[0062] Preparation Example 2

[0063] 15 parts by mass of butyl acrylate and 15 parts by mass of nitrile rubber (powdered nitrile rubber P83) are put into an internal mixer, mixed and stirred evenly; the mixed raw materials are added to a grinder, and 25 parts by mass of ammonium sulfate, 14 parts by mass of silica fume, 7 parts by mass of sorbitol and 24 parts by mass of dihydrate gypsum are added to the grinder, and ground to 25 μm to obtain adhesive B.

[0064] Preparation Example 3

[0065] 15 parts by mass of butyl acrylate and 12 parts by mass of nitrile rubber (powdered nitrile rubber P83) are put into an internal mixer, mixed and stirred evenly; the mixed raw materials are added to a grinder, and 33 parts by mass of ammonium sulfate, 13 parts by mass of silica fume, 7 parts by mass of sorbitol and 20 parts by mass of dihydrate gypsum are added to the grinder, and ground to 25 μm to obtain adhesive C.

[0066] Example 1

[0067] Magnesium powder, inorganic carbon source, adhesive A and sawdust in a mass ratio of 50:20:10:20 were added to a proper amount of water (the volume ratio of water to other components was about 1:2), mixed, stirred for 1 hour, mechanically processed into granules, and vacuum dried for 6 hours to obtain filler 1#. The particle size of filler 1# was 8 to 12 mm.

[0068] The inorganic carbon source is calcium carbonate, sodium carbonate and sodium bicarbonate in a mass ratio of 2:1:2.

[0069] Example 2

[0070] Magnesium powder, inorganic carbon source, adhesive B and sawdust in a mass ratio of 55:15:5:25 were added to an appropriate amount of water (the volume ratio of water to other components was about 1:2), mixed, stirred for 1 hour, mechanically processed into granules, and vacuum dried for 6 hours to obtain filler 2#. The particle size of filler 2# was 8 to 12 mm.

[0071] The inorganic carbon source is calcium carbonate, sodium carbonate and sodium bicarbonate in a mass ratio of 1:1:2.

[0072] Example 3

[0073] Magnesium powder, inorganic carbon source, binder C and sawdust in a mass ratio of 50:10:10:30 were added to a proper amount of water (the volume ratio of water to other components was about 1:2), mixed, stirred for 1 hour, mechanically processed into granules, and vacuum dried for 6 hours to obtain filler 3#. The particle size of filler 3# was 8 to 12 mm.

[0074] The inorganic carbon source is calcium carbonate, sodium carbonate and sodium bicarbonate in a mass ratio of 2:1:2.

[0075] Example 4

[0076] The preparation method of the filler refers to Example 1, and the only difference from Example 1 is that the "wood chips" are replaced with "corn cob powder" to prepare filler 4#.

[0077] Example 5

[0078] The preparation method of the filler is similar to that of Example 1, and the only difference from Example 1 is that "wood chips" are replaced with "polyurethane foam" to obtain filler 5#.

[0079] Example 6

[0080] The preparation method of the filler refers to Example 1, and the only difference from Example 1 is that the "wood chips" are replaced by "multi-surface hollow balls" to prepare filler 6#.

[0081] Example 7

[0082] The preparation method of the filler refers to Example 1, and the only difference from Example 1 is that the "wood chips" are replaced by "molecular sieves" to prepare filler 7#.

[0083] Example 8

[0084] The preparation method of the filler is similar to that of Example 1, and the only difference from Example 1 is that "sawdust" is replaced with "zeolite" to obtain filler 8#.

[0085] Example 9

[0086] The preparation method of the filler is similar to that of Example 1, and the only difference from Example 1 is that "wood chips" are replaced with "pumice" to obtain filler 9#.

[0087] Comparative Example 1

[0088] The preparation method of the filler is similar to that of Example 1, and the only difference from Example 1 is that no inorganic carbon source is added to obtain filler D1.

[0089] Comparative Example 2

[0090] The preparation method of the filler is similar to that of Example 1, and the only difference from Example 1 is that no sawdust is added to obtain filler D2.

[0091] Comparative Example 3

[0092] The preparation method of the filler is similar to that of Example 1, and the only difference from Example 1 is that the magnesium powder is replaced with iron powder to obtain filler D3.

[0093] Evaluation of sewage treatment effect

[0094] The fillers prepared in each embodiment and comparative example are added Figure 1 The effect evaluation test of sewage treatment was carried out in the reactor shown.

[0095] Figure 1 The reactor shown is a packed column reactor, comprising a reactor body 1 and a three-phase separator 2 arranged on the top of the reactor body 1. The reactor body 1 is a closed organic glass container with an inner diameter of 10 cm and a volume of 5 L. The three-phase separator 2 is used to separate mud and water vapor; a water inlet 3 is arranged at the bottom of the reactor body 1, a water outlet 4 is arranged at the top of the reactor, and a reflux inlet 6, a sampling port 5 and a reflux outlet 7 are arranged on the side wall of the reactor body 1 from bottom to top.

[0096] The fillers prepared in each embodiment and comparative example are loaded into the reactor body 1. Nitrogen-containing wastewater without an organic carbon source is simulated and prepared, and the dissolved oxygen in the wastewater is controlled below 3 mg / L by nitrogen oxygen drive. The sludge that has been domesticated in the laboratory for one year is inoculated on the filler, and the simulated water distribution is used for secondary domestication. After that, the wastewater is pumped into the reactor with a peristaltic pump, and the inlet nitrate nitrogen concentration is shown in Table 1; it is operated in continuous flow mode, without deoxygenation facilities or processes, the temperature is controlled at 20-25°C, the reflux ratio is 5, the system pH stable range is shown in Table 1, and the dissolved oxygen is lower than 0.3 mg / L; when the hydraulic retention time HRT=4h, it is continuously operated for 2 months, during which the nitrate nitrogen effluent concentration is measured, and the nitrate nitrogen removal rate of the effluent is calculated. The results are shown in Table 1.

[0097] The nitrate nitrogen concentration was tested using the ion chromatography test method (HJ / T84-2001); the nitrate nitrogen removal rates in the effluent in Table 1 are average values.

[0098] The autotrophic denitrifying bacteria used in the above-mentioned sewage treatment effect evaluation process were taken from the sludge screened and enriched after one year of domestication in the laboratory.

[0099] Table 1

[0100]

[0101]

[0102] The reactor loaded with the fillers prepared in Examples 1-9 was operated continuously for 2 months, and the effluent quality was stable, indicating that the autotrophic denitrification process using the porous material coupled with magnesium powder filler as an electron donor provided by the present invention can efficiently remove nitrate nitrogen from sewage.

[0103] No inorganic carbon source was added to the filler prepared in Comparative Example 1, resulting in a lack of inorganic carbon source in the reactor. The inorganic carbon source can also act as a pH regulating component. The lack of inorganic carbon source will cause the pH of the autotrophic denitrification reaction process to decrease, deviate from the optimal pH range, and thus lead to a significant decrease in denitrification efficiency.

[0104] In the filler prepared in Comparative Example 2, no porous material was added, and microorganisms were not easy to attach and grow, resulting in a significant decrease in denitrification efficiency.

[0105] In the filler prepared in Comparative Example 3, the metal component magnesium is replaced by iron. The denitrification efficiency is good in the early stage of the operation of the device, which is slightly worse than that of Example 1, but the difference is not obvious. However, during the operation, the surface of the filler gradually turns iron red, and the denitrification efficiency continues to decrease. It is speculated that trivalent iron deposits accumulate on the surface of the filler during the reaction and affect the subsequent utilization of the filler.

[0106] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A porous material coupled with a magnesium powder filler, characterized in that: The composition comprises the following components in parts by weight: Magnesium: 40-60 parts; Porous materials: 20-35 parts; Inorganic carbon source: 5-20 parts; Adhesive: 5 to 10 parts.

2. The filler according to claim 1, characterized in that The porous material includes at least one of a porous structure biological material, a porous structure organic material, and a porous structure inorganic material; Preferably, The porous structure biomaterial comprises a porous structure natural biomaterial containing cellulose, preferably at least one of sawdust, corn cobs, and grapefruit peels; And / or, the porous structure organic material includes at least one of polyurethane foam material, polyhedral hollow spheres of organic material, and ball rings of organic material; And / or, the porous structure inorganic material includes at least one of molecular sieve, zeolite, activated carbon, pumice, rock wool, porous ceramics, and perlite.

3. The filler according to claim 1 or 2, characterized in that: The inorganic carbon source includes at least one of calcium carbonate, sodium carbonate, sodium bicarbonate, magnesium carbonate, zinc carbonate and ferrous carbonate.

4. The filler according to any one of claims 1 to 3, characterized in that The adhesive comprises the following components in percentage by mass: 25-33% ammonium sulfate, 13-15% silica fume, 7-10% sorbitol, 12-15% nitrile rubber, 12-15% butyl acrylate and 20-24% dihydrate gypsum; Preferably, the preparation method of the adhesive comprises: putting butyl acrylate and nitrile rubber into an internal mixer for internal mixing; adding the internally mixed raw materials, ammonium sulfate, silica fume, sorbitol and dihydrate gypsum into a grinder, grinding, and obtaining the adhesive.

5. The method for preparing a filler according to any one of claims 1 to 4, characterized in that: include: The filler is prepared by mixing magnesium powder, porous material, inorganic carbon source, binder and water, stirring, granulating and vacuum drying.

6. The preparation method according to claim 5, characterized in that: The stirring time is 1 to 2 hours; And / or, the vacuum drying time is 5 to 7 hours; And / or, the filler particle size is 8 to 12 mm.

7. An autotrophic denitrification reactor, characterized in that: The invention comprises a filler as claimed in any one of claims 1 to 4 or a filler prepared by the preparation method as claimed in claim 5 or 6.

8. The reactor according to claim 7, characterized in that The filler occupies 60% to 80% of the volume of the reactor.

9. The reactor according to claim 7 or 8, characterized in that In the reactor, autotrophic denitrifying bacteria using magnesium and hydrogen as electron donors are selected as the dominant bacteria.

10. Use of the filler according to any one of claims 1 to 4, the filler prepared by the preparation method according to claim 5 or 6, and the reactor according to any one of claims 7 to 9 in sewage treatment; especially in treating sewage with a dissolved oxygen concentration lower than 3.0 mg / L and a ratio of COD concentration to nitrate nitrogen concentration less than 3.

Citation Information

Patent Citations

  • Aerobic bio-particle carrier for directly removing ammonia nitrogen from sewage with low carbon nitrogen ratio and preparation method thereof

    CN103145234A

  • Preparation method of denitrifying nitrogen removal material

    CN109592797A

  • Method for treating sewage by biological filter based on sponge iron composite filler

    CN111620514A

  • Nitrate nitrogen denitrifying treatment material, method of producing the same, and method of removing nitrate nitrogen

    EP1419996A1

  • Wastewater treatment apparatus and wastewater treatment method

    JP2006231184A